Correction to: Pictorial review of multiparametric MRI in bladder urothelial carcinoma with variant histology: pearls and pitfalls. - Arita, Yuki; Woo, Sungmin; Ruby, Lisa; Kwee, Thomas C.; Shigeta, Keisuke; Ueda, Ryo; Nalavenkata, Sunny; Edo, Hiromi; Miyai, Kosuke; Das, Jeeban; Causa Andrieu, Pamela I.; Vargas, Hebert Alberto (Abdominal Radiology, 2025)
The article addresses a correction regarding the authorship of a previously published work in Abdominal Radiology, specifically noting the omission of co-author Lisa Ruby. The correction ensures that the authorship accurately reflects all contributors involved in the research. The publisher, Springer Nature, emphasizes its neutrality concerning jurisdictional claims in published maps and institutional affiliations. This correction is important for maintaining the integrity of academic authorship and acknowledgment in scholarly publications.